2012
DOI: 10.1002/art.33425
|View full text |Cite
|
Sign up to set email alerts
|

Disorders in angiogenesis and redox pathways are main factors contributing to the progression of rheumatoid arthritis: A comparative proteomics study

Abstract: Objective. To clarify the pathogenesis of rheumatoid arthritis (RA) by comparing protein expression in fibroblast-like synoviocytes (FLS) from patients with RA with that in FLS from normal subjects, using proteomics analysis.Methods. Proteins extracted from primary cultures of FLS obtained from 50 patients with RA and 10 normal subjects were analyzed by automated 2-dimensional nano-electrospray ionization liquid chromatography tandem mass spectometry. Differentially expressed proteins were screened by 2-sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 34 publications
4
46
0
Order By: Relevance
“…Not unexpectedly, the FoxP3/RORc ratio in the inactive RA groups was the highest while that in the active RA groups was the lowest (figure 1F). We used the Disease Activity Score 28 (DAS28) to explore the relationship between disease activity of RA21 and the FoxP3/RORc ratio. Inverse correlation of the FoxP3/RORc ratio and the DAS28 was observed with r=−0.78, p<0.0001 (figure 1G).…”
Section: Resultsmentioning
confidence: 99%
“…Not unexpectedly, the FoxP3/RORc ratio in the inactive RA groups was the highest while that in the active RA groups was the lowest (figure 1F). We used the Disease Activity Score 28 (DAS28) to explore the relationship between disease activity of RA21 and the FoxP3/RORc ratio. Inverse correlation of the FoxP3/RORc ratio and the DAS28 was observed with r=−0.78, p<0.0001 (figure 1G).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, using SELDI-TOF-MS method to identify the proteomic shift in laryngeal carcinoma serum, Cheng et al and Liu group reported different findings and conclusions that few proteins were found to vary in concert, and the discrepancies might be due to their technical problems such as varying ability of mass spectrometry to identify a particular protein [14], [15]. Thus, successful application of proteomic technologies to biomedical and clinical research is leading to the discovery of disease-specific biomarkers for diagnosis and treatment monitoring, providing insight into the underlying pathologies and allowing identification of novel therapeutic targets [12]. In the current study, we used 2 chromatographic methods coupled with MS to detect differentially expressed proteins and thereby greatly raised the number of detectable proteins.…”
Section: Discussionmentioning
confidence: 99%
“…All MS/MS spectrums were identified by using SEQUEST [v.28 (revision 12), Thermo Electron Corp.] against the human UniProtKB/Swiss-Prot database (Release 2011_12_14, with 20249 entries), as previously described [12]. To reduce false positive identification results, a decoy database containing the reverse sequences was appended to the database.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was approved by the local research ethics committee, with informed consent from all the participants concerned. Synovial tissue was isolated enzymatically and primary cultured according to the method previously described [25]. All FLS cells of passages 3-5 were used for the experiment.…”
Section: Patients and Fls Cell Culturementioning
confidence: 99%